Research hotbeds: A practice for scientific development in universities - Huamani Torres, Ruth (2022)
The study carried out seeks to explain how the seedbeds; they are part of the formative research program of the universities to fine-tune research methods, strengthen critical thinking; problem solving and promoting innovation. In this sense, the study was developed under the quantitative approach of cross-sectional scope; descriptive-correlational level; with the non-probabilistic-intentional sampling type. With the participation of 1116 university students of the formative research program. Obtaining as a result that the relevant point that the training sessions in the framework of the formative research showed to the research hotbeds is that they were related to the particular interest of the participants for an effective management of the bibliographic reference managers. There is an interest in accessing scientific databases; and optimally handle software such as Zotero, EndNote and Mendeley; in order to manage scientific information through storage, organization, managing citations and bibliographic references. Coming to the conclusion that the seedbeds represent in the formative research of the universities; a program to stimulate the development of research skills in students of various cycles through the development of courses related to research methodology, scientific writing, use of computer tools for managing references.